Metal-organic frameworks: structure, properties, methods of synthesis and characterization. (March 2016) - Butova, V V; Soldatov, M A; Guda, A A; Lomachenko, K A; Lamberti, C
Abstract : This review deals with key methods of synthesis and characterization of metal-organic frameworks (MOFs). The modular structure affords a wide variety of MOFs with different active metal sites and organic linkers. These compounds represent a new stage of development of porous materials in which the pore size and the active site structure can be modified within wide limits. The set of experimental methods considered in this review is sufficient for studying the short-range and long-range order of the MOF crystal structure, determining the morphology of samples and elucidating the processes that occur at the active metal site in the course of chemical reactions. The interest in metal-organic frameworks results, first of all, from their numerous possible applications, ranging from gas separation and storage to chemical reactions within the pores. The bibliography includes 362 references.